Analisis Tenaga Kerja, Pendidikan Dan Tingkat Kemiskinan Pengaruhnya Terhadap Pertumbuhan Ekonomi Di Provinsi Jawa Tengah Tahun 2013 - Melati, Melina Ambar, Dr. Didit Purnomo, M, Si (2016)
This study entitled "Analysis of Labor, Education and Poverty Rate Effect on Economic Growth in Central Java province in 2013". The purpose of this study was to analyze the effect of variable amount of labor, education and poverty to economic growth in Central Java province in 2013. Data used in this research is secondary data, regional gross domestic product (GDP), total employment, education (AHM) and the level of poverty in the province of Central Java. The analytical method used was Ordinary Least Squares (OLS) is to determine the direction and magnitude of the effect of one independent variable (independent) on the dependent variable (dependent). The results of this study can be concluded that the variable labor has significant influence on the GDP with a coefficient of 0.901549. Things are not the same is also available on the education variable (AHM), which does not have a significant influence on the GDP with a coefficient of 0.030048. While the poverty level variables have a significant influence on the GDP with coefficient of .055922 ..